2020
DOI: 10.3389/fnagi.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Level Influences White Matter Microstructure in Postmenopausal Women

Abstract: Aerobic exercise has both neuroprotective and neurorehabilitative benefits. However, the underlying mechanisms are not fully understood and need to be investigated, especially in postmenopausal women, who are at increased risk of age-related disorders such as Alzheimer's disease and stroke. To advance our understanding of the potential neurological benefits of aerobic exercise in aging women, we examined anatomical and functional responses that may differentiate women of varying cardiorespiratory fitness using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 119 publications
1
8
0
Order By: Relevance
“…However, the authors reported a trending association between higher cardiorespiratory fitness and lower myelin damage (radial diffusivity) in the right cingulum. Similarly, in postmenopausal women, Harasym et al (2020) found a significant relationship between higher fitness and higher axonal integrity (axial diffusivity) in the hippocampal segments of the cingulum. Bracht et al (2016) found that greater amounts of device‐measured engagement in physical activity was associated with greater myelination (myelin water fraction), but not FA, in the right parahippocampal cingulum in healthy young adults.…”
Section: Hippocampal Wmmentioning
confidence: 94%
“…However, the authors reported a trending association between higher cardiorespiratory fitness and lower myelin damage (radial diffusivity) in the right cingulum. Similarly, in postmenopausal women, Harasym et al (2020) found a significant relationship between higher fitness and higher axonal integrity (axial diffusivity) in the hippocampal segments of the cingulum. Bracht et al (2016) found that greater amounts of device‐measured engagement in physical activity was associated with greater myelination (myelin water fraction), but not FA, in the right parahippocampal cingulum in healthy young adults.…”
Section: Hippocampal Wmmentioning
confidence: 94%
“…While we observed that VO2max relates positively with GABA+ and Glx when both groups were combined (see Figure 3 ), we did not find any significant relationships when only considering younger and older cohorts separately. Another study in postmenopausal women (age = 59 ± 3 years) also did not find any relationship between VO2max and GABA+ from the motor cortex ( 64 ). From our previous section, we note that Glx plays a critical role in brain functioning and cognition in older participants.…”
Section: Discussionmentioning
confidence: 88%
“…No correlation was found between age and the depth of SAI, but we did find that SAI was significantly weaker in Study H, which sampled older individuals (59 ± 3 years), than in study A, which sampled a younger cohort (21 ± 2 years). Specifically, Harasym et al [ 22 ] (i.e., study H) studied a group of post-menopausal women while Tsang et al [ 16 ] (i.e., Study A) studied a sample of young males and females. This finding may support a previous meta-analysis reporting a significant decline in SAI with age [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from healthy control participants (n = 170, 73 female) from eight studies that were conducted between 2014 and 2020 in the Neurophysiology and Imaging Laboratory (McMaster University, Hamilton ON, Canada) were included in this retrospective study [14,[16][17][18][19][20][21][22]. Studies and participant demographics are displayed in Table 1.…”
Section: Subjectsmentioning
confidence: 99%